Teacher Capacity Building in Developing Project-Based Learning Model in Toraja - P, Suhenrik; Salam, Supardi; Ramly, Rizal Arizaldy; B, Eka Ariaty; Marwan, Marwan; Alfira, Evi; Mustari, Ulul Azmi (Jurnal Perjuangan dan Pengabdian Masyarakat : JPPM, 2025)
The capacity-building program for teachers in developing Project-Based Learning (PjBL) in schools in Toraja aims to improve the quality of education through a more creative, contextual, and participatory learning approach. This activity provides a platform for teachers to understand the principles of PjBL, design curriculum-based learning projects, integrate Toraja local wisdom into projects, enhance classroom management skills for project-based learning, and develop assessment and reflection skills. Through this community service program, teachers are expected to improve professional and pedagogical competence, students gain meaningful learning experiences, and an innovative learning culture is fostered in schools.